(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
It is the fact that polymer plants are increasing by their useful features and also more beneficial sides. With conducting special chemical reactions, adding more different characteristical additional chemicals, peculiar extruder equipments and changing Sex and MI measurements we can obtain more influential and modern bimodal polymers. In this article, we researched about how to develop bimodal polymers by some important changes